2014
DOI: 10.1080/13607863.2014.977775
|View full text |Cite
|
Sign up to set email alerts
|

Inner strength – associated with reduced prevalence of depression among older women

Abstract: Objectives: The aim of this study was to explore if inner strength is independently associated with a reduced prevalence of depression after controlling for other known risk factors associated with depression. Methods: A population-based cross-sectional study was performed, where all women living in Åland, a Finnish self-govern island community in the Baltic Sea, aged 65 years or older were sent a questionnaire including the Geriatric Depression Scale and the Inner Strength Scale along with several other quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 36 publications
(54 reference statements)
3
33
0
Order By: Relevance
“…Questioning about strengths came nearer the end of the interview once an in‐depth understanding of the participant and their life had been gained. Given this context towards the end of the interview, this situation gave us a unique opportunity to reflect in action (Boman et al, ) with them, identifying what could be strengths drawn from their own narrative. For example, Nellie had talked about the issues she had faced in being an advocate for people in her retirement village and standing up to the management.…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Questioning about strengths came nearer the end of the interview once an in‐depth understanding of the participant and their life had been gained. Given this context towards the end of the interview, this situation gave us a unique opportunity to reflect in action (Boman et al, ) with them, identifying what could be strengths drawn from their own narrative. For example, Nellie had talked about the issues she had faced in being an advocate for people in her retirement village and standing up to the management.…”
Section: The Studymentioning
confidence: 99%
“…Applying this theory to explore the inner strength of community dwelling older women, they found women with higher inner strength, as measured using the Inner Strength Scale (Lundman et al, 2011), had better physical health, and their social relationships were more satisfying. Subsequent studies have found stronger inner strength is associated with less risk of experiencing depression and feeling lonely in older women (Boman, Gustafson, Häggblom, Fischer, & Nygren, 2015;Boman, Lundman, Nygren, Årestedt, & Fishcer, 2017). Janssen, Regenmortel and Abma (2011) do not provide a definition of what they mean by strength, but identified sources of strength that give rise to resilience in older people receiving longterm community care.…”
mentioning
confidence: 99%
“…However, it is known that symptoms of depressive disorders, depression and loneliness are strongly associated with poor health and well‐being and with each other (Bergdahl, Allard, Lundman, & Gustafson, ; Boman et al., ; Cacioppo, Huges, Waite, Hawkley, & Thisted, ; Dahlberg, Andersson, McKee, & Lennartsson, ). Depression has also previously shown associations with weak inner strength (Boman et al., ; Viglund et al., ) and other known health resources are also related to poor mental health and depression (e.g. resilience, sense of coherence, purpose in life and self‐transcendence) (Lundman et al., ; Netuveli, Wiggins, Montgomery, Hildon, & Blane, ; Windle, Markland, & Woods, ).…”
Section: Discussionmentioning
confidence: 95%
“…However, it is known that symptoms of depressive disorders, depression and loneliness are strongly associated with poor health and well-being and with each other (Bergdahl, Allard, Lundman, & Gustafson, 2007;Boman et al, 2015a;Cacioppo, Huges, Waite, Hawkley, & Thisted, 2006;Dahlberg, Andersson, McKee, & Lennartsson, 2015). Depression has also previously shown associations with weak inner strength (Boman et al, 2014;Viglund et al, 2014) Hildon, & Blane, 2008;Windle, Markland, & Woods, 2008). One explanation of the results could be that persons who strive to develop resources to cope with demands will usually develop more of them (Bircher, 2005) and mental ill health could diminish this striving.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation